National Microfinance Strategies - Duflos, Eric (World Bank, Washington, DC, 2012)
An increasing number of countries are developing national microfinance strategies, bringing the topic to the forefront of national development priorities. Over 30 countries, most in Africa, now have such strategies. This trend appears to be fueled by microfinance's heightened visibility and new development modalities that favor sector-wide approaches and policy work. Developing a national microfinance strategy usually involves four stages: (i) conducting a diagnostic/gap analysis of the microfinance sector; (ii) consulting with stakeholders (more or less extensively); (iii) drafting a document, usually by a consultant in cooperation with government; and (iv) adopting and implementing the strategy, including approval by a governmental body and, in some cases, defining action steps to put the strategy into practice.